Time‐dependent modeling of slow slip events and associated seismicity and tremor at the Hikurangi subduction zone, New Zealand. Issue 1 (27th January 2014) - Bartlow, Noel M.; Wallace, Laura M.; Beavan, R. John; Bannister, Stephen; Segall, P.
<x xml:space="preserve">Abstract</x> We present a time‐dependent slip model of 12 slow slip events (SSEs) occurring in the Hikurangi margin of New Zealand during 2010 and 2011. This model is obtained by inverting daily GPS solutions from GeoNet's continuous GPS network on the North Island and northern South Island. We compare the properties of these SSEs to observations in Japan, Cascadia, and Mexico and find that Hikurangi SSEs have comparatively large amounts of slip (up to 27 cm), high slip rates (up to 1.4 cm/d), and a large range of depths (10–40 km), durations (7–270 days), and sizes (Mw 5.9–6.9). We further investigate the relationship between the Cape Turnagain SSE and an associated seismic swarm and find that observations are consistent with stress triggering outside the slowly slipping region; however, other explanations cannot be ruled out. We also compare slip during the long‐term Manawatu SSE with the tremor epicenters found by Ide (2012) and note that tremor locations are offset in the downdip direction relative to the slipping region, similar to observations in the Bungo Channel of Japan and Guerrero, Mexico.